Performance of Ganoderma lucidum Biomass and β-Glucan as functional feed for African catfish (Clarias gariepinus) on immuno-oxidative defenses - Yerima, Grema; Norhidayah Mohd Taufek; Zul Ilham; Muhamad Hafiz Abd Rahim; Nurul Aqilah Mohd Zaini; Nor Hidayah Ismail; Nafisyah, Ayu Lana; Wan-Mohtar, Wan Abd Al Qadr Imad (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study evaluated the effects of dietary Ganoderma lucidum biomass and β-glucan on growth, organ function, and immune response in African catfish (Clarias gariepinus) over a 60-day feeding period. The experiment consisted of five groups: T1 (10 g biomass/3 g β-glucan), T2 (15 g biomass/3 g β-glucan), T3 (20 g biomass/3 g β-glucan), C1 (formulated feed without biomass/β-glucan), and C2 (commercial feed), respectively. Post-feeding analyses were performed on various liver function parameters, including serum total protein, albumin, globulin, bilirubin, phosphate, magnesium, cholesterol, and glucose levels, as well as liver metabolic enzymes. The kidney function was assessed via serum sodium, potassium, chloride, total carbon dioxide, anion gap, and urea, while the immunomodulatory effects of the diet were investigated on white blood cell counts (WBC) and absolute leucocyte counts. Results demonstrated that the combined diet of G. lucidum biomass and β-glucan significantly increased body weight and length, improved kidney and liver function (as indicated by favorable changes in serum biochemical markers and liver enzymes), and enhanced immune parameters by stabilizing white blood cell and leukocyte counts of African catfish. Group T2, containing 15 g G. lucidum biomass and 3 g β-glucan, exhibited the best performance in providing higher growth, effective liver and kidney functioning, and enhanced immunity in African catfish (C. gariepinus), making it a recommended concentration in this study.